SMART TOURISM IN KEDONDONG DISTRICT TO MAKE IT EASIER FOR TOURISTS - Baiti Ilma; Muhamad Muslihudin (YHMM PUBLISHING, 2023)
Tourist attractions in Kedondong District have the potential for very many tourist destinations in various tourist attractions that can be visited from natural attractions, one of which is swimming pool tourism, crystal guava, mountains and others. However, the lack of information makes tourists not know that Kedodondong sub-district has lots of good and interesting tourist spots for holidays and taking pictures. This is the reason that underlies tourists not knowing about tourism in the Kedondong sub-district, therefore to make it easier for tourists to find out, they need a web-based application. By using this mobile web application, it can make it easier for tourists to find information on tourist attractions in the Kedondong sub-district and of course it is easy to visit tours in the Kedondong sub-district and in using this mobile web application, in making web-based information systems using distance technology to tourist locations as well as regarding information on these tourist attractions can use the information system. The results of this research on tourist attractions can help search for tourist objects and can promote tourism potential in the Kedondong sub-district as well as lift the Kedondong regional economy and make tourism information dissemination easier and more efficient.